Facile gamma radiolytic methodology for TiO2-rGO synthesis: effect on photo-catalytic H-2 evolution - Gupta, Bhavana; Melvin, Ambrose A.; Matthews, Tom; Dhara, S.; Dash, Sitaram; Tyagi, A. K. (International Journal of Hydrogen Energy, 2015)
TiO2 (P25) decorated reduced graphene oxide (rGO) is synthesized by gamma-radiolytic technique using water-ethanol solvent medium. Visible light absorpdon was confirmed by UV-Visible spectroscopy. Photoluminescence (PL) study revealed a decline in electron-hole recombination rate signalled by a sharp fall in luminescence of TiO2. Under such scenario, electron transfer from TiO2 conduction band to the conjugated sheet becomes a preferred pathway in the presence of rGO, which is further confirmed by photocurrent measurement. TiO2 -rGO composite with 1 wt. % rGO was found to be the best composition in terms of visible light absorption, while retaining TiO2 crystallinity. Transmission electron microscopy and Raman spectroscopic studies confirmed the coating of rGO sheet with TiO2 nanoparticles. TiO2 -rGO was found to show about 150 times higher photocatalytic H-2 generation under 250 W UV-Visible light irradiation than pristine TiO2. In addition to this, TiO2 -rGO composite shows hydrogen production yield of 35 mu mol/h.g under visible light (lambda = 400 nm) irradiation. Thus gamma-radiolysis can be considered to be a viable technique, which helps in synthesizing photocatalytically active nanocomposite with high H-2 evolution rate. In the light of these interesting aspects, a detail investigation is carried out to study the effect of rGO concentration and illumination time on photocatalytic yield. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: gamma-radiolysis; H-2 production; Photocatalysis; Reduced graphene oxide; TiO2